New species and taxonomic rearrangements of Anostostomatid Crickets (Orthoptera: Stenopelmatoidea: Anostostomatidae) from the Neotropics - Cadena-Castañeda, Oscar J.; Cortés-Torres, Carolina (Zootaxa, 2013)
This paper describes and illustrates a new species of the genus Anabropsis (Anostostomatidae: Anabropsinae) from Co-lombia, we group the species of this genus were grouped into three groups: Mexicana, Alata and Aptera. A brief review of the genus Apotetamenus (Anostostomatidae: Lutosinae) is also given including a new species from the Colombian rain-forest; also A. clipeatus is redescribed and a new distribution data are provided. Finally A. politus (Brunner, 1915) is des-ignated as synonym of A. clipeatus.